A retrospective comparison of dental treatment under general anesthesia versus non-pharmacological approach in patient with special health care needs - Pornpailin Kasemkhun (2022)
Background/purpose: The unmet dental needs are still at the highest rate in patients with special health care needs (SHCN) owing to their physical conditions, lack of cooperation, anxiety and dental fear. This study was aimed to investigate the differences in characteristics and outcomes of dental treatment between general anesthesia (GA) and non-pharmacological approach (NP) in patients with SHCN. Materials and methods: This study reviewed the dental chart records of SHCN patients from 2005 to 2019. The dental chart records were divided into two subgroups: GA and NP groups. The demographic data, recall behavior and treatment outcomes were analyzed and compared between groups. The comparisons between groups were analyzed by Pearson's chi-squared test, Fisher's exact test and Mann–Whitney U test at a significant level of 0.05. Results: Two hundred and sixty-one patients aged 2.2–43.1 years with mean age 14.22 ± 8.64 years old were included. The proportion of cases treated under GA (62%) and NP (38%) was 1.6:1. General anesthesia group had significantly higher in mean ages, caries experience, definitely negative behavior and treatment needs than NP group (P < 0.001). Moreover, recall rates in GA group were significantly lower than NP group (P < 0.001) without a significant difference in regularity. New caries occurrence (P = 0.015) with faster rate (P = 0.035), and behavior changes was significantly found in GA group (P = 0.007) after 24 months of recall. Conclusion: Patients with SHCN who were at older age and had high caries experience with definitely negative behavior and numerous treatment needs were more justifiably for GA. A significant new caries occurrence with faster rate tended towards SHCN patients who underwent GA.